Index of Alpha/Theta Ratio of the Electroencephalogram: A New Marker for Alzheimer’s Disease - Schmidt, Magali; Kanda, Paulo; Basile, Luis; da Silva Lopes, Helder F.; Baratho, Regina; Demario, Jose; Jorge, Mario; Nardi, Antonio; Machado, Sergio; Ianof, Jessica N.; Anghinah, Renato; Nitrini, Ricardo (Frontiers in Aging Neuroscience, 2013)
Objective: We evaluated quantitative EEG measures to determine a screening index to discriminate AD patients from normal individuals. Methods: Two groups of individuals older than 50 years, comprising a control group of 57 normal volunteers and a study group of 50 patients with probable AD, were compared. EEG recordings were obtained from subjects in a wake state with eyes closed at rest for 30 min. Logistic regression analysis was conducted. Results: Spectral potentials of the alpha and theta bands were computed for all electrodes and the alpha/theta ratio calculated. Logistic regression of alpha/theta of the mean potential of the C3 and O1 electrodes was carried out. A formula was calculated to aid the diagnosis of AD yielding 76.4 % sensitivity and 84.6 specificity for AD with an area under the ROC curve of 0.92. Conclusions: Logistic regression of alpha/theta of the spectrum of the mean potential of EEG represents a good marker discriminating AD patients from normal controls.